Program Pemberdayaan Kelompok Usaha bagi Penyandang Difabel Melalui Pemanfaatan Digital Marketing: Business Group Empowerment Program for People with Disabilities through the Utilization of Digital Marketing - Indardi Indardi; M. Thesa Ghozali; Salmah Orbayinah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Lazismu Sedayu is a service partner who formed the KUBE for the disabled group in Argosari Village. This service will conduct online marketing training and workshops by utilizing digital marketing and social media, as well as training on content creation and product branding targeting all business fields. The program is hoped to continue even though this community service activity has been completed so that disabled groups can be independent. The independence improvement program was carried out in the form of providing counseling on organizational strengthening and administration, obtaining PIRT permits, as well as halal and hygienic food products, while the marketing workshop was in the form of counseling on the use of digital marketing for business actors, and public speaking. The disabled community who participated in this community service activity were enthusiastic about the material presented, as evidenced by the many participants who asked questions and gave responses during the discussion and question and answer sessions. The results of testimonials from several disabled communities said that the material presented was beneficial; the disabled community could upgrade their knowledge and skills, which would help develop their business. The implementation of community service with the topic of increasing the independence of the disabled community went smoothly. The counseling program was very effective in increasing the knowledge of the disabled community. Through this activity, it is hoped that people with disabilities can always be optimistic and productive because their efforts will become widely known by the public through digital marketing strategies.